Manajemen Strategi Kepala Sekolah Dalam Peningkatan Mutu Pendidikan Di SDN 24 Gadut Kecamatan Tilatang Kamang - Maiyudin, Maiyudin (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This study uses a qualitative method whose focus is the Strategic Management of the Principal of SDN 24 Gadut in improving the quality of educators and education personnel, the quality of facilities and infrastructure and the quality of management. The results obtained in this study indicate that the Principal Strategy of SDN 24 Gadut in improving the quality of educators and education personnel through routine supervision of principal supervision, delegation of authority, training, upgrading, seminars, technical guidance, workshops, and training, and evaluating performance of educators and education personnel. The strategy of the Principal of SDN 24 Gadut in an effort to improve the quality of facilities and infrastructure is carried out by coordinating through budget meetings at the beginning of the year, gradually fulfilling facilities, conducting comparative studies and fulfilling computer facilities for management strategies, the Principal of SDN 24 conducting planning, implementing programs and activities monitoring and evaluation. The findings were obtained by the Principal of SDN 24 Gadut to find solutions in the process of improving quality and managing school management even better. Starting from the process of accepting new students to graduation that involves all parties. In addition, the school is always oriented towards the satisfaction of the community and school residents both internally and externally and the school together continuously improves the quality of education through various activities that involve the community and school residents. In addition to support from the government, SDN 24 Gadut also received full support from parents and the community for the progress of the school